Access to justice in clientelist networks - Shami, Mahvish (2022)
Despite its importance for poverty reduction, the poor face barriers when accessing justice. However, the literature, looking mostly at developed countries, focuses on the institutional underpinnings of these restrictions, and thus ignores social structural barriers. This paper deals with one type of social barrier; clientelism and its impact on poor clients’ access to justice. I argue that asymmetric power distribution enables patrons to bar clients from accessing formal institutions. Such barriers can’t be rectified through institutional reforms. Making use of an original dataset from Pakistan this paper recommends an unorthodox policy solution; increasing connectivity. I demonstrate how exit options, brought about through connectivity, alter bargaining powers, thereby limiting patrons’ ability to block clients from accessing formal justice institutions